From Brand Credibility to Skincare Purchase Intention: The Mediating Role of Fear of Missing Out in E-Commerce - N. Azizia Gia Mutiarasari; Krisnayanti Aditasari; Wahyu Eka Kiswardani (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze how brand credibility influences skincare purchase intention among Gen Z consumers using e-commerce platforms and examine the mediating role of fear of missing out (FoMO). Four hypotheses are proposed: brand credibility positively influences FoMO and purchase intention, FoMO positively influences purchase intention, and FoMO mediates the relationship between brand credibility and purchase intention. This study used a quantitative cross-sectional design with an online survey of 285 Gen Z consumers in Indonesia who had searched for or purchased local skincare products through e-commerce platforms. Respondents were selected using non-probability purposive sampling and snowball sampling techniques. Brand credibility, FoMO, and skincare purchase intention were measured using an adapted multi-item Likert scale, and the data were analyzed using PLS-SEM, including evaluation of the measurement model and structural model. The results indicate that brand credibility increases FoMO and directly strengthens purchase intention. At the same time, FoMO is the strongest predictor of skincare purchase intention and partially mediates the effect of brand credibility on purchase intention. These findings indicate that brand credibility in the context of social commerce not only serves as a rational signal that reduces risk but also as a FoMO trigger that accelerates purchase intention